Effect of Ankle Pumping Exercise to Ankle Brachial Index in Type 2 Diabetes Mellitus Patients with Ulcer - Widjajalaksmi; Elida Ilyas; Em Yunir; Arini Setiawati; Tjie Haming Setiadi (Indonesian Journal of Physical Medicine & Rehabilitation, 2012)
Objectives: To analyze the effect of ankle pumping exercise and other factors such as gender, age, duration of Diabetic Mellitus, nutritional status, history of smoking, hypercholesterolemia, ulcer degreeand HbA1c to Ankle Brachial Index (ABI) in type 2 Diabetes Mellitus patients with diabetic ulcer.Methods: The quasi experimental design study with consecutive sampling and one-week interval of intervention was conducted in this study. Analysis of changes in pre-post test ABI used paired t-testwhile other factors were measured with multiple regression.Results: Ankle pumping effect to right foot after exercise as 0.048 while ABI 0,017 on left foot and ABI 0.038 after exercise on both feet. It was not a statistically significant increase on both feet (p>0.05). The relations of multifactors to ABI : Gender 0.47(p 0.829), age 51.32 (p 0.743), duration of DM 83.16(p 0.490), BMI 21.82 (p 0.452), history of smoking 0.47 (p 0.769), hypercholesterolemia 0.11 (p 0.195), degree of ulcer 3.74 (p 0.635), HbA1c 0.89 (p 0.798).Conclusions: There is statistically no effect of ankle pumping exercise to ABI. We also did not find an effect of gender, age, and duration of DM, nutritional status, history of smoking, history of hypercholesterolemia, ulcer grade and HbA1c to increase of ABI in diabetic subjects with foot ulcer after ankle pumping exercise. Nevertheless, we found a sufficiently noted increase of systolic blood pressure of Dorsal Pedis Artery and Posterior Tibia Artery after ankle pumping exercise in type 2 DM subjects although this not statistically significant.Keywords : Diabetes Mellitus, diabetic ulcer ankle pumping, ankle-brachial index.